2008
DOI: 10.1073/pnas.0808066105
|View full text |Cite
|
Sign up to set email alerts
|

Distinct size distribution of endogenous siRNAs in maize: Evidence from deep sequencing in the mop1-1 mutant

Abstract: Small RNAs from plants are known to be highly complex and abundant, with this complexity proportional to genome size. Most endogenous siRNAs in Arabidopsis are dependent on RNA-DEPEN-DENT RNA POLYMERASE 2 (RDR2) for their biogenesis. Recent work has demonstrated that the maize MEDIATOR OF PARAMUTATION1 (mop1) gene is a predicted ortholog of RDR2. The mop1 gene is required for establishment of paramutation and maintenance of transcriptional silencing of transposons and transgenes, suggesting the potential invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
198
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 190 publications
(226 citation statements)
references
References 32 publications
26
198
2
Order By: Relevance
“…2A). The reduction in b1TR-siRNAs in mop1-1 was consistent with the global reduction in 24-nt siRNAs previously reported in the mop1-1 mutant (14). SNPs are present in four of the seven repeats, and they allowed us to map distinct siRNAs to more than one repeat (Table S1), indicating that multiple repeats are transcribed and processed into siRNAs in B′.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…2A). The reduction in b1TR-siRNAs in mop1-1 was consistent with the global reduction in 24-nt siRNAs previously reported in the mop1-1 mutant (14). SNPs are present in four of the seven repeats, and they allowed us to map distinct siRNAs to more than one repeat (Table S1), indicating that multiple repeats are transcribed and processed into siRNAs in B′.…”
Section: Resultssupporting
confidence: 69%
“…2A). A total of 33 and 3 b1TR-siRNAs were present in the WT and mop1-1 libraries, respectively, from a total of 13 million reads (14). These small RNAs had characteristics of siRNAs because they were predominantly 24 nt in size and examples were found that matched to both strands ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous hc-siRNAs comprise a major portion of the regulatory small RNA pool in key angiosperm model organisms including A. thaliana (Lu et al, 2006), O. sativa (Jeong et al, 2011), and Zea mays (Nobuta et al, 2008). Most hc-siRNAs are 24 nucleotides in length and are thought to function in RNAdirected DNA methylation, which couples 24-nt siRNA production from heterochromatic regions to targeting of chromatin-associated nascent non-coding RNA transcripts.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%